Analysis of User Experience and Perceived Value on Repurchase Intention With E- Satisfiction as an Intervening Variable in the Traveloka Application : Users of the Traveloka Application in Medan City - Suci Veny Beauty; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (International Journal of Economics and Management Sciences, 2025)
The development of the digital-based travel industry is growing rapidly in Indonesia, including in the city of Medan. Traveloka is one of the most widely used platforms for booking tickets and accommodations. However, despite its large user base, there are still complaints about the user experience of the traveloka application which will have an impact on user satisfaction. This study aims to analyze user experience and perceived value on repurchase intention through e-satisfaction for application users in Medan city. The type of research conducted is associative research. The population for this study consists of residents of Medan city who use the Traveloka application, with a sample size of 125 respondents. The sampling technique used is non-probability sampling with a purposive sampling method. The data analysis technique employed in this study is structural equation modeling (SEM) using the Smart PLS version 4.0 analysis tool. Research results User experience has a positive but insignificant effect on repurchase intention. Perceived value has a positive and significant effect on repurchase intention. User experience has a positive and significant effect on e-satisfaction. Perceived value has a positive and significant effect on e-satisfaction on the Medan city traveloka application. E- satisfaction has a positive and significant effect on repurchase intention. User experience has a positive and significant effect on repurchase intention through e-satisfaction. Perceived value has a positive and significant effect on repurchase intention through e-satisfaction.